A review of the Chilean Egoliini (Coleoptera: Trogossitidae) with description of a new species of Necrobiopsis Crowson - Arias, Elizabeth T.; Slipinski, Adam; Lawrence, John F.; Elgueta, Mario (Zootaxa, 2009)
The Chilean members of the little known tribe Egoliini (Trogossitidae, Trogossitinae) are revised, keyed and illustrated. The tribe is represented in Chile by three species of the genus Acalanthis Erichson, and a single species of Necrobiopsis Crowson (N. shangrila sp. n.), a genus known previously from Australia. All Chilean species of Egoliini occur in temperate forests and are often collected by canopy fogging.